The Roles of Mercury in Intracytoplasmic Sperm Injection - Feng, Z. C.; Hu, Howard H.; Agca, Yuksel (Journal of Vibration Testing and System Dynamics, 2026)
Intracytoplasmic sperm injection (ICSI), microinjection of a single spermatozoon into an oocyte, is a routine procedure in assisted reproduction programs. This procedure uses fine control of small bore microinjection needles and precise volume control via hydraulic syringe pumps. In many early experiments mercury is placed within the injection system because its high surface tension in the system facilitates the injection procedure. However, mercury is cytotoxic and therefore alternative fluids or approaches are needed. Here we examine the main properties of mercury and their impact on the various aspects of ICSI. We conclude that the small momentum diffusivity of mercury is the most important contributing factor that facilitates the ICSI procedures.